The implementation of good corporate governance at Baitut Tamwil Muhammadiyah (BTM) Tegal - Hidayat, Arip (Journal of Islamic Economics Management and Business (JIEMB), 2020)
Purpose – Author studied the implementation of good corporate governance in a context of microfinance institution. Corporate Governance is a very strategic determining factor for the progress of a company in order to continuously increase value and maintain an ongoing and sustainable growth process.Method – Sources of data used in this study were taken from primary data and secondary data. Apart from interviews, other primary data source categories include reviewing, reading several global financial reports and standard operating procedure (SOP). Secondary data were obtained from books as a complement to primary data sources. Additional secondary data source of this research was obtained by conducting literature reviews.Result – Modern pondok of Tazakka uses at least six different waqf program as a financial source of their activities. These programmes are asset waqf, cash waqf, productive waqf, benefits waqf, profession waqf, and transfer of rights waqf. The programmes help the pondok to be more autonomous and able to provide various benefits for the scholars of the pondok and the people surround it. Implication – The results show that the Baitut Tamwil Muhammadiyah (BTM) implemented a good corporate governance.Originality – This study has enriched an empirical study of corporate governance in microfinance institution in Indonesia.